UMPSA synergy expands Technology-Focused TVET - Nor Salwana, Mohammad Idris (UMPSA, 2024)
KUALA LUMPUR, 3 May 2024 - An estimated 100,000 Bumiputera Technical and Vocational Education and Training (TVET) trainees are projected to secure jobs with salaries RM3,000 higher than the minimum wage.